The structure and in vitro starch digestibility of wheat starch-glycerol monopalmitin complexes: the effect of heating conditions and water content - Jiao, Fengping; Liu, Zesong; Ni, Jing; Yu, Jinglin; Wang, Shujun; Liu, Xia (Frontiers in Nutrition, 2023)
The effects of the heating conditions and water content on the structure and digestibility of wheat starch (WS)-glycerol monopalmitin (GMP) complexes were investigated. The results showed that the higher water content and the heating conditions of 90 °C for 60 min after 100 °C for 10 min favor the formation of more WS-GMP complexes with the greater short-range order, although the thermal transition temperatures of GWS-GMP-100 complexes are not significantly affected by the water content. Only the type Ⅰ complexes were formed under the heating conditions of 90 °C for 60 min. The heating conditions of 90 °C for 60 min after 100 °C for 10 min facilitates the formation of type Ⅱ complexes, and the amounts of type Ⅱ complexes increased with increasing water content. The digestion rates of WS-GMP complexes decreased slightly with increasing water content, and the extent of starch amylolysis of WS-GMP complexes significantly decreased after heating further at 90 °C compared with that only heating at 100 °C. The digestibility of complexes is mainly related to structural order rather than the number of complexes. This study is helpful to further understand starch-lipid complexes by showing that heating conditions and water content influence the formation of WS-GMP complexes.